Prevalence, Risk Factors, Harm Perception, and Attitudes Toward E-cigarette Use Among University Students in Qatar: A Cross-Sectional Study - Kurdi, Rana; Al-Jayyousi, Ghadir Fakhri; Yaseen, Manar; Ali, Aatefeh; Mosleh, Neama; Abdul Rahim, Hanan F. (Frontiers in Public Health, 2021)
Background: Electronic cigarette (e-cigarette) use is becoming popular worldwide especially among youth. Research reported that university students have poor knowledge and misconceptions about the health risks of e-cigarettes, which may lead students to use them even in populations where prevalence of cigarette smoking is relatively low. Understanding attitudes of college students towards the use of e-cigarettes is important for an effective tobacco prevention policy. In this study, we assessed the prevalence of e-cigarette use among university students as well as their knowledge and attitudes towards e-cigarettes. Methodology: We conducted a cross-sectional study among Qatar University students using a self-administered online questionnaire. Descriptive univariate analysis of all variables was conducted as well as a bivariate analysis to check the association of e-cigarette use with selected variables. A binary logistic regression was conducted to assess predictors of e-cigarette use. Results: A total of 199 students completed the questionnaire. The prevalence of e-cigarette use among students was found to be 14% where 32% of them were daily users. Approximately 42% of the participants agreed that ‘e-cigarettes are less harmful to health compared to traditional cigarettes, and 45.7% of them agreed that ‘e-cigarettes can prevent smoking traditional cigarettes. Among users, 75% think that they are less harmful than conventional cigarettes and almost 40% indicated that they used these products because they would help them quit smoking cigarettes. The prevalence of e-cigarettes use was 16.2% among males and and 12.8% among females, which showed no significant difference between the two genders. Females were more likely to use e-cigarettes because they “don’t smell” (P-value=0.023). The study showed a significant association between e-cigarette use and knowledge items (P-value < 0.05) and having a smoker among siblings or friends. At the multivariate analysis level, only the friends’ effect remained significant after controlling for the other variables (OR= 7.3, P-value=0.000). Conclusion: Our research found that university students have inadequate knowledge and misconceptions in regards to e-cigarettes use, especially among users. Effective smoking prevention policy and educational interventions are needed to enhance awareness among university students about the health effects associated with e-cigarettes use.